Identification of disease-associated DNA methylation in B cells from Crohn's disease and ulcerative colitis patients - Lin, Zhenwu; Hegarty, John P; Yu, Wei; Cappel, Jon A; Chen, Xi; Faber, Pieter W; Wang, Yunhua; Poritz, Lisa S; Fan, Jian-Bing; Koltun, Walter A (Digestive diseases and sciences, 2012)
BACKGROUND: Changes in the methylation status of inflammatory bowel disease (IBD)-associated genes could significantly alter levels of gene expression, thereby contributing to disease onset and progression. We previously identified seven disease-associated DNA methylation loci from intestinal tissues of IBD patients using the Illumina GoldenGate BeadArray assay. AIMS: In this study, we extended this approach to identify IBD-associated changes in DNA methylation in B cells from 18 IBD patients [9 Crohn's disease (CD) and 9 ulcerative colitis (UC)]. B cell DNA methylation markers are particularly favorable for diagnosis due to the convenient access to peripheral blood. METHODS: We examined DNA methylation profiles of B cell lines using the Illumina GoldenGate BeadArray assay. Disease-associated CpGs/genes with changes in DNA methylation were identified by comparison of methylation profiles between B cell lines from IBD patients and their siblings without IBD. BeadArray data were validated using a bisulfite polymerase chain reaction (PCR)-based restriction fragment length polymorphism (RFLP) method. To verify that observed changes in DNA methylation were not due to virus transformation, we compared specific CpG DNA methylation levels of GADD45A and POMC between B cell lines and matching peripheral blood B lymphocytes from five individuals. RESULTS: Using this approach with strict statistical analysis, we identified 11 IBD-associated CpG sites, 14 CD-specific CpG sites, and 24 UC-specific CpG sites with methylation changes in B cells. CONCLUSIONS: IBD- and subtype-specific changes in DNA methylation were identified in B cells from IBD patients. Many of these genes have important immune and inflammatory response functions including several loci within the interleukin (IL)-12/IL-23 pathway.
Keywords: Humans; lidé středního věku; Colitis, Ulcerative; regulace genové exprese; ulcerózní kolitida; interleukin-23 - podjednotka p19; interleukin-2; Female; dospělí; Crohn Disease; lidé; B-lymfocyty; Interleukin-2; buněčné linie; Interleukin-23 Subunit p19; Adult; DNA Methylation; metylace DNA; ženské pohlaví; Cell Line; Gene Expression Regulation; Male; Middle Aged; B-Lymphocytes; Crohnova nemoc; mužské pohlaví